Constructing a maqasid (objective) based performance measurement index for Islamic banks - Tarique, Kazi Md.; Islam, Rafikul; Mohamed, Mustafa Omar; Abdul Razak, Dzuljastri; Hamdan, Hamdino (International Journal of the Analytic Hierarchy Process, 2020)
The current study aims to develop a Maqasid al-Shari’ah (Objective of Islamic Law) based new performance evaluation index for Islamic banks. In order to achieve the objective, the current study at first took twelve semi-structured interviews of academics and practitioners specialized in Islamic banking and finance (IBF) to select the variables for the index. Afterwards, to validate the selected variables a focus group discussion was arranged consisting of five experts in IBF. Then to prioritize the selected Maqasid variables, item and sub-items, analytic hierarchy process (AHP) is employed. The number of respondents in this case was thirty consisting of industry experts, Shari’ah scholars and academics. Lastly, an index is developed and tested on some selected Islamic banks of Malaysia and Bangladesh to rank their Maqasid based performance. The findings revealed that RHB Islamic bank ranked top among the sampled Islamic banks. Overall, Malaysian Islamic banks performed better than Bangladeshi Islamic banks. The novelty of this study lies in its contribution to the theory of Maqasid al-Shari’ah with respect to banking performance evaluation. The index is expected to assist the policy makers, practitioners and other stakeholders to tally Islamic banks performance in line with Maqasid al-Shari’ah and thus adopt necessary policy changes accordingly.